(3NWH YHOGdQMje Hf fHGJI hGHfg eMeOs - (3YHO GdQMje Hf eMeO Hf ESeGYjd GHf fHGJI GdaGQbj, CHhjMji,J (B374 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdZfhj GdQbj bQGAI Ydjg aj SfI CQHY hYTQjf hNeSeGFI bGd(B: (3CNHQfG GdTjN GdNWjH Hf fHGJI GdaGQbj Yf CHjg CHj WGgQ eMeO Yf CHjg CHj jMji YHOGdQMje fHGJI QMeI Gddg bGd(B: (3NWHI jPcQ ajgG GSJbHGd GdSfI haVd s
(3BNQgG (B:s
(3eHJhQ, jfJgj CKfGA NWHI dCHj WGgQ eMeO Hf YHOGdQMje Hf fHGJI hChd gPg GdNWHI GdeHJhQI(B: (3GdMeO ddg GdcQje Whdg, GdYXje Uhdg GdeQghH YOdg GdeWdhH aVdg s
(3QhGjI CHhESMGb EHQGgje Hf eMeO Hf fHgGf GdZfhj GdQbis
(3HBNQgG SeGY Ydi GdTjN YdGA GdOjf CHj GdMSf Ydj Hf Ydj Hf eSeGQ GdeYQha HGHf GdUjQaj JGQjNg SfI (B736(3g`s
(3Ke Jedc SfI (B809(3g`s
(3hHChdgG Jedc SfI (B775(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B347 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B211s
Keywords: (3GdCOHs